Special role of corn flour as an ideal carbon source for aerobic denitrification with minimized nitrous oxide emission - Zhu, Shuangyue; Zheng, Maosheng; Li, Can; Gui, Mengyao; Qian Chen; Ni, Jinren (Bioresource TechnologyBioresource Technology, 2015)
Much effort has been made for reducing nitrous oxide (N2O) emission in wastewater treatment processes. This paper presents an interesting way to minimize N2O in aerobic denitrification by strain Pseudomonas stutzeri PCN-1 with help of corn flour as cheaper additional carbon source. Experimental results showed that maximal N2O accumulation by strain PCN-1 was only 0.02% of removed nitrogen if corn flour was used as sole carbon source, which was significantly reduced by 52.07-99.81% comparing with others such as succinate, glucose, acetate and citrate. Sustained release of reducing sugar from starch and continuous expression of nosZ coding for N2O reductase contributed to the special role of corn flour as the ideal carbon source for strain PCN-1. Further experiments in sequencing batch reactors (SBRs) demonstrated similarly efficient nitrogen removal with much less N2O emission due to synergy of the novel strain and activated sludge, which was then confirmed by quantitative PCR analysis. (C) 2015 Elsevier Ltd. All rights reserved.